Numerical investigation of silted-up dam-break flow with different silted-up sediment heights. Issue 2 (19th January 2023) - Gu, Zhenghua; Wang, Tinghui; Meng, Wenkang; Yu, Ching-hao; An, Ruidong
Abstract: The silted-up sediment in the reservoir may have a significant influence on the propagation of dam-break flows. In this paper, a three-dimensional numerical simulation of the silted-up dam-break flow is carried out. In this paper, simulations of three-dimensional silted-up dam-break flow are carried out. A kind of Eulerian–Eulerian two-fluid model (TFM), coupled level set and volume of fluid (CLSVOF) methods, is presented. In order to calculate the motions of the air–water interface and the sediment simultaneously, kinetic particle theory (KPT) and computational fluid dynamics (CFD) are combined. The rheology-based constitutive equations of sediment are also considered to simulate scouring and deposition. In addition, a partial-slip boundary condition (BC) for the velocity of the sediment phase at stationary walls is implemented. The simulation results of the benchmark case demonstrate that the proposed model can effectively simulate the silted-up dam-break flow while taking into account multi-interface capturing problems. Subsequently, the simulations of the silted-up dam-break flow over dry are investigated numerically in a three-dimensional long channel. The simulated results reveal that, in the dam-break flows, the silted-up sediment height has a significant influence on wave propagation, dynamic pressure loads, sediment transport, and sediment deposition. HIGHLIGHTS: Three-dimensional simulation of silted-up dam-break flow is carried out. The air–water interface movement is captured by CLSVOF method. A Eulerian–Eulerian multiphase model coupling kinetic particle theory and computational fluid dynamics is used. The rheology-based constitutive equations of sediment are considered. The effect of the silted-up sediment height during a dam-break flow is investigated.